Total hip arthroplasty in the treatment of degenerative disorders in rural and urban patients – A retrospective, randomised and controlled study - Kazimierz Rąpała; Aleksandra Truszczyńska; Adam Tarnowski (Annals of Agricultural and Environmental Medicine, 2015)
Introduction Farming is hard work which may lead to overstrain and osteoarthritis of the hip and knee. Hip osteoarthritis has been rarely discussed in the Polish literature.